Estudo sobre um instrumento de escrita designado auto-retrato para a expressão do indivíduo - Passalacqua, Claudia Loewenberg (2007)
This paper investigates a writing tool, namely Self-Portrait, whose aim is to collect data on an individual´s psychic expression. It comprises a 35 question questionnaire, made up of open-ended directed and self directed questions. The order of the answers is random, and some questions may be answered many times while others may never be answered. This writing tool was used in a group of psychologically disturbed women, who had been referred to a state health center in the outskirts of São Paulo city. Most women belong to the low and low-middle classes, with very few years of schooling, but, in general, with working experience, in the 30-60 age bracket. They were referred to the state health center by psychiatrists and psychologists, due to chief complaints such as depression, stress, etc. The group was coordinated by the research-psychologist and by an occupational therapist. Initially, the treatment aimed to engage the group in manual tasks and provide them with some space in which they could air their problems. On presenting the questionnaire to the women, the research-psychologist read them the iinstructions, their questions, and explained the procedures as well the terms of agreement. The questionnaire was kept in the health center and apart from the subjects and the therapist, nobody else had access to them. Due to all the conditions of public service assiduity, punctuality, follow-up sessions, among others the use of the self-portrait was not constant in all the sessions and wasn´t equally used by all the women. Since the activities were decided on by the group and took place in the inicial phases of the group´s functioning, it was hard to maintain group cohesion, as some women answered the questionnaires in each session while others took longer to write. These differences were inevitable once all the women shared a common physical space. The self-potrait questions aimed at categorizing those women´s realities: routine, family and professional life, emotional, psychological and existencial aspects and world knowledge. Moreover, the written account of their life experiences served as an oulet for the free expresson of their reality The therapeutical aim of the self-portrait was to investigate the efficiency of writing as a mechanism to surface the underlying phychic information, despite the fact that this written account was produced by women of varying literacy levels. Writing differs from speech in that writing can be crystalized in time, once it can be registered permanently. Besides, writing entails a distinctive connection between conscious and uncounscious contents. It leads the individual into an introspective journey, allowing for the re-enactment of past experiences. By means of this exercise, processes and memories are brought to the consciosness mind and may be modified when experienced again. This study falls into the category of case study, once it focus on aspect´s of a specific woman´s life: someone who, upon joining the group, felt incredbly miserable and was, from the very begining, given special treatment by the research-psychologist. The same rules which applied for the self-portrait within the group were used in private consultations. Semantic networks, formed by words that were repeated along the text, were used for the analysis of the written accounts, following Jung's Model of Typology